Hate crime in football: how racism is destroying the beautiful game - Awan, Imran; Zempi, Irene (Bristol University Press, 2023)
Rates of hate crime within football have been increasing, despite the visibility of anti-racist actions such as ‘taking the knee’. With a unique collection of testimonies, this book shows that hostility is a daily occurrence for some professional football players, ranging from online threats to physical intimidation and violence at football matches. Bringing a range of perspectives to this widespread problem, leading academics, practitioners and policy makers shed light on the best strategies to tackle racism, homophobia, transphobia and misogyny in football